Pelatihan Pembuatan Hiasan Dinding dengan Bentuk Pegunungan pada Sekolah Budi Agung - Juli Atika; Rani Hermita; Muslida Murti (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Making wall hanging crafts reflects the desire to create a space that has a unique visual character and feel. The process of making this wall decoration is inspired by various interior design styles. The concept of mountains in wall decoration design becomes an attractive focal point because it creates a calm, beautiful atmosphere and is inspired by the beauty of nature. The background for making wall decorations with a mountain concept is based on the desire to bring natural elements into the room and provide a unique aesthetic touch. Through wall decorations with a mountain concept, it is hoped that residents can feel the wonder of nature, experience peace, and enjoy the beauty that provides added value. on the interior design of the room at Budi Agung Medan School. making wall hanging crafts reflects the desire to create a space that has a unique visual character and feel. The process of making this wall decoration is inspired by various interior design styles. The concept of mountains in wall decoration design becomes an attractive focal point because it creates a calm, beautiful atmosphere and is inspired by the beauty of nature limitation in designing the design. The Budi Agung Medan School teacher's room is a teacher's room in a private school building. This site was chosen because the space in the design object requires spatial adaptation to accommodate new user activities. Apart from that, in terms of changes in working systems, uncomfortable circulation, insufficient storage requirements, and the image of the teacher's room is not yet prominent, these are the problems found. Apart from that, this is a limitation in designing the design.